Effect of polymer content and temperature on mechanical properties of lightweight polymer concrete. (10th November 2020) - Heidarnezhad, Fatemeh; Jafari, Khashayar; Ozbakkaloglu, Togay
Highlights: Lightweight polymer concrete (LWPC) is studied as a material of high strength-to-weight ratio. Mechanical properties of LWPCs tested at different temperatures are obtained. Optimum conditions to develop desirable material properties are identified. Statistical analyses are conducted to understand the influence of each parameter on mechanical properties of LWPC. Abstract: This study investigates the mechanical properties of lightweight polymer concrete (LWPC) containing four different polymer ratios (10%, 12%, 14%, and 16%) tested at three different temperatures (−15 °C, +5 °C, and +25 °C) using destructive and non-destructive tests. In addition, a series of expressions are suggested to predict the splitting-tensile, flexural and impact strength of LWPC based on the main parameters and compressive strength. The analysis of variance (ANOVA) method was also used to determine relative contributions of the experimental parameters. The results of the destructive tests show that increasing the polymer ratio caused an increase in the compressive, splitting-tensile, and impact strengths, and energy absorption of LWPC. With decreasing the temperature from +25 °C to −15 °C, the compressive, splitting-tensile, flexural strengths, and elastic modulus (EM) increased, whereas the energy absorption, impact energy, and ductility decreased. The findings of this research provide beneficial information toward understanding the behavior of LWPC and its safe use in engineering applications where a material of high strength-to-weight ratio is required.